Are derivatives better dead or alive in Zmbabwe - Chikoko, Laurine (Midlands State University, 2014)
This research comes at a time when Zimbabweans are looking for practical and compatible solution in the quest to resolve the transitory challenges facing the economy. It is the objective of this paper to compliment all other national policies and initiatives to bring to the people of Zimbabwe a better, sound and innovative financial systems. Thus the paper particularly intends to offer as another powerful tool which gives information on whether derivatives are a building block in the resuscitation of a distressed economy and if not, are they better dead